Polyethylene glycol-polyester based temperature-sensitive hydrogel delivering mesenchymal stem cell-derived exosomes enhances acute skin wound healing - Wei, Zining; Ren, Jie; Hu, Jianshe; Wei, Haiming (Frontiers in Bioengineering and Biotechnology, 2025)
Skin wound healing remains a significant clinical challenge. Conventional dressings have limitations in maintaining an optimal wound microenvironment and preventing secondary injury. In this study, we developed a Poly (lactic-co-glycolic acid)-poly (ethylene glycol)-poly (lactic-co-glycolic acid) (PLGA-PEG-PLGA, PPP) thermosensitive hydrogel loaded with mesenchymal stem cell-derived exosomes (MSC-Exos) to enhance acute skin wound healing by prolonging exosome retention and bioavailability at the wound site. The hydrogel exhibited a rapid sol-gel transition at approximately 32 °C, demonstrating good mechanical stability (storage modulus (G′) > loss modulus (G″)) and self-healing properties at physiological temperature. In vitro experiments revealed that PPP/Exos showed superior biocompatibility with L929 mouse fibroblast cells (L929 cells) and human umbilical vein endothelial cells (HUVECs), significantly promoting cell proliferation and vascular tube formation. In a Sprague-Dawley (SD) rat full-thickness skin defect model, the PPP/Exos group markedly accelerated wound closure. By day 14, wound closure reached 98.6% in the PPP/Exos group, compared with 87.6% in the control group. Histopathological examination further revealed that PPP/Exos treatment effectively enhanced granulation tissue formation, attenuated inflammatory responses, facilitated re-epithelialization, and substantially increased collagen deposition. Through immunohistochemical analysis, we identified three mechanisms underlying the enhanced wound healing: promoted angiogenesis, accelerated myofibroblast differentiation, and reduced inflammation. Collectively, the PPP/Exos thermosensitive hydrogel, with its excellent biocompatibility, injectability, and sustained exosome release characteristics, significantly promotes wound healing through synergistic “angiogenesis-tissue remodeling-anti-inflammation” effects. This system offers a promising therapeutic strategy for clinical wound management and establishes a solid foundation for applications in regenerative medicine.